Application of Response Surface Methodology to Study the Effects of Brisket Fat, Soy Protein Isolate, and Cornstarch on Nutritional and Textural Properties of Rabbit Sausages - Joseph M. Wambui; Edward G. Karuri; Margaret M. M. Wanyoike (International Journal of Food Science)
The effects of brisket fat, soy protein isolate, and cornstarch on chemical and textural properties of rabbit sausages were studied using surface response methodology. Sausage samples were prepared using a five-level three-variable Central Composite Rotatable Design with 16 combinations, including two replicates of the center point, carried out in random order. The level of brisket fat (BF), soy protein isolate (SPI), and cornstarch (CS) in the sausage formulation ranged within 8.3–16.7%, 0.7–2.3%, and 1.3–4.7%, respectively. Increasing BF decreased moisture and ash contents but increased protein and fat contents of the sausages (p<0.05). Increasing SPI increased moisture content but decreased ash and carbohydrate contents of the sausages (p<0.05). Increasing CS increased carbohydrate content (p<0.05). Increasing BF increased hardness, adhesiveness, cohesiveness, and chewiness but decreased springiness (p<0.05). SPI addition increased springiness but decreased adhesiveness, cohesiveness, and chewiness (p<0.05). In conclusion, varying the levels of BF and SPI had a more significant effect on chemical and textural properties of rabbit sausages than CS.